Good governance and good aid allocation. - Epstein, Gil S.; Gang, Ira N. (Journal of Development Economics, 2009)
We model the aid allocation process as a rent-seeking contest between two countries and investigate the effects of differing allocation rules on recipients' behavior in a simple framework. We investigate the aid allocation mechanism design that attempts to increase the governance quality of potential recipient countries: the potential recipients spend costly resources improving governance, while the donor country allocates the fund based on their governance quality. The paper compares two mechanisms: one uses a simple winner-takes-all tournament to award the entire available purse to the country with the best governance; while under the other aid is distributed among countries in proportion to their governance qualities. The paper shows the second mechanism outperforms the first only if competing countries are sufficiently asymmetric. Moreover, the recipient who is most effective in governance - and stands to benefit the most from development assistance - has interests opposite to those of the donor. In addition, the paper shows that if the donor country allocates the fund based on both governance and the levels of poverty, it may result in a poverty trap: the leaders of potential recipient countries deliberately allocate funds away from the poorest so as not to better their position in order to receive more aid. Copyright (c) 2009 Elsevier B.V.